PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI MA MA ’ARIF SELOREJO BLITAR - Muhammad Iqbal Baihaqi (Universitas Islam Balitar, 2015)
The objectives of this study are to see the effect of: principal leadership, performance motivation, and principal leadership and performance motivation toward teacher ’ performance. The study used correlationl design involving 23 teachers as sample. Instruent used for the study is questionnaire. The study found the following findings. Descriptive statistic showed that three aspects being investigated are good, in terms of principal leadership, teacher competence, and teachers ’ performance. Results of hypothesis testing showed that significant effect was contributed in terms of (1) principal leadership toward teacher ’s performance (r=2.599, p=0.05), (2) performance motivation towards teacher performance (r= 3.160, p=0.05), and (3) leadership and performance motivation towards teacher performance (F = 8.48, p=0.05).